Cybersecurity career master plan : proven techniques and effective tips to help you advance in your cybersecurity career - Auger, Gerald; Scott, Jaclyn; Helmus, Jonathan; Nguyen, Kim (Packt Publishing, Limited, 2021)
Get started with cybersecurity and progress with the help of expert tips to get certified, find a job, and moreKey FeaturesLearn how to follow your desired career path that results in a well-paid, rewarding job in cybersecurityExplore expert tips relating to career paths and certification optionsAccess informative content from a panel of experienced cybersecurity expertsBook DescriptionCybersecurity is an emerging career trend and will continue to become increasingly important. Despite the lucrative pay and significant career growth opportunities, many people are unsure of how to get started. This book is designed by leading industry experts to help you enter the world of cybersecurity with confidence, covering everything from gaining the right certification to tips and tools for finding your first job. The book starts by helping you gain a foundational understanding of cybersecurity, covering cyber law, cyber policy, and frameworks. Next, you'll focus on how to choose the career field best suited to you from options such as security operations, penetration testing, and risk analysis. The book also guides you through the different certification options as well as the pros and cons of a formal college education versus formal certificate courses. Later, you'll discover the importance of defining and understanding your brand. Finally, you'll get up to speed with different career paths and learning opportunities. By the end of this cyber book, you will have gained the knowledge you need to clearly define your career path and develop goals relating to career progression. What you will learn: Gain an understanding of cybersecurity essentials, including the different frameworks and laws, and specialties; Find out how to land your first job in the cybersecurity industry; Understand the difference between college education and certificate courses; Build goals and timelines to encourage a work/life balance while delivering value in your job; Understand the different types of cybersecurity jobs available and what it means to be entry-level; Build affordable, practical labs to develop your technical skills; Discover how to set goals and maintain momentum after landing your first cybersecurity job; Who this book is for: This book is for college graduates, military veterans transitioning from active service, individuals looking to make a mid-career switch, and aspiring IT professionals. Anyone who considers cybersecurity as a potential career field but feels intimidated, overwhelmed, or unsure of where to get started will also find this book useful.